A feasibility study of pelvic morphology for curved implants. Issue 10 (October 2016) - Zakariaee, Roja; Schlosser, Colin L.; Baker, Daniel R.; Meek, Robert N.; Coope, Robin J.N.
Abstract: Objectives: We hypothesize that inserting a curved intramedullary internal fixation device which follows curved osseous fixation paths (OFPs) would be more versatile and mechanically stronger than straight screws for fixation of pelvic ring and acetabular injuries. This study characterizes the dimensions of curved OFPs of the pelvic ring and acetabulum and suggests design parameters for such a curved device. Methods: CT scans of intact pelves of 50 female and 50 male subjects were studied using MIM Maestro™ and Solidworks™ to determine the constriction points (smallest cross sections) and the tightest radii of curvature (RoC) in the anterior column, posterior column, iliosacral and pubic symphysis OFPs. Results: The constriction point diameters for the superior pubic ramus and supra-acetabular areas were 13 ± 3 mm and 12 ± 3 mm, respectively. The anterior column RoC was greater than 65 mm in all cases. The minimum observed RoC for the path from one ilium, across the SI joint, the sacrum and to the other ilium was 71 mm, with 99% of the cases having a RoC of at least 80 mm, in both the inlet and outlet views. Conclusion: This study shows that if a flexible implant which could be stiffened once in place was available, it would enable the use of larger and longer fixation taking advantage of the pelvis's curved intracortical spaces. Even for dysmorphic pelves, accessible tunnels support a long, strong, curved fixation device.